2007
DOI: 10.1093/brain/awm214
|View full text |Cite
|
Sign up to set email alerts
|

Multiple sclerosis: T-cell receptor expression in distinct brain regions

Abstract: Multiple sclerosis (MS) is an inflammatory demyelinating disease where T cells attack the brain and the spinal cord. It is known that often particular T-cell clones are expanded in the target tissue, but it is still unknown, whether identical T-cell clones are present at distinct anatomical sites, or whether the T-cell spectrum is locally diverse. Therefore we compared the T-cell receptor (TCR) repertoire in distinct lesions and normal-appearing white matter (NAWM) from post-mortem brains of four MS patients. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
154
2
2

Year Published

2008
2008
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 176 publications
(166 citation statements)
references
References 54 publications
8
154
2
2
Order By: Relevance
“…Moreover, CDR3 nucleotide sequences encoding TcRs isolated from different lesions of individual MS brains revealed silent nucleotide changes implying that distinct T cell clones with identical antigen-specificity can be detected within MS lesions [33]. This CDR3 spectratyping confirms that infiltration of CD8 T cells in the lesions is selective, rather than stochastic.…”
Section: Cd8 T Cells and Their Subsets In Msmentioning
confidence: 52%
“…Moreover, CDR3 nucleotide sequences encoding TcRs isolated from different lesions of individual MS brains revealed silent nucleotide changes implying that distinct T cell clones with identical antigen-specificity can be detected within MS lesions [33]. This CDR3 spectratyping confirms that infiltration of CD8 T cells in the lesions is selective, rather than stochastic.…”
Section: Cd8 T Cells and Their Subsets In Msmentioning
confidence: 52%
“…There is an oligoclonal expansion of CD8 1 T cells in the MS plaques [20,21] and CSF [22]. Additionally, there is an enrichment in highly differentiated CD8 1 T cells in the CSF of patients with early MS, suggesting that CD8 1 T cells are activated and antigen-driven early in the course of MS [23].…”
Section: Introductionmentioning
confidence: 99%
“…Axonal damage is also present [61,62] , and the degree of this was associated with abundance of microglia and CD8 + T cells [63] . Clonally expanded CD8 + T cells are present usually at the lesion edge, as well as in the perivascular infiltrates, indicating a specific antigen response and also possibly responsible for damages to neurons through cell dependent cytotoxicity [64][65][66][67] . It was also demonstrated that clonal γδ T cells are present in MS lesions [68] .…”
Section: Table 1 Chemokines Receptor Expression On T Cells and T Cellmentioning
confidence: 99%